2019
DOI: 10.1136/bjsports-2018-100170
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of injuries at the Pyeongchang 2018 Paralympic Winter Games: a prospective cohort study of 6804 athlete days

Abstract: ObjectiveTo describe the epidemiology of sports injury at the Pyeongchang 2018 Paralympic Winter Games.Methods567 athletes from 49 countries were monitored daily for 12 days over the Pyeongchang 2018 Paralympic Winter Games (6804 athlete days). Injury data were obtained daily from teams with their own medical support (41 teams and 557 athletes) and teams without their own medical support (8 teams and 10 athletes) through two electronic data capturing systems.Results112 of 567 athletes (19.8%) reported a total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
86
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(98 citation statements)
references
References 24 publications
4
86
0
Order By: Relevance
“…The studies from the Paralympic Games have reported considerably lower IPs ranging from 11.6% to 23.8%. 2,5,6,8,27,28 Noteworthy is that 85% of the injuries in the present study occurred outside competition and that one-third were classified as severe. This is a concern as most athletes do not have on-site medical support outside competition.…”
Section: Sports-related Injuriesmentioning
confidence: 58%
“…The studies from the Paralympic Games have reported considerably lower IPs ranging from 11.6% to 23.8%. 2,5,6,8,27,28 Noteworthy is that 85% of the injuries in the present study occurred outside competition and that one-third were classified as severe. This is a concern as most athletes do not have on-site medical support outside competition.…”
Section: Sports-related Injuriesmentioning
confidence: 58%
“…A few web-based large epidemiological studies concerning injury characteristics in summer and winter Paralympic Games were conducted twice each year 4–6 23. The first large prospective epidemiological study on injuries in impaired athletes that expressed injury rates and injury proportions per 1000 athlete days was reported following the London 2012 Summer Paralympic Games 6.…”
Section: Discussionmentioning
confidence: 99%
“…These injury cases included 61 athletes who had participated in WR and WB and incurred 14.9 and 12.8 injuries per 1000 athlete days at the Rio 2016 Paralympic Games 4. Additionally, a survey on the winter competitions reports 142 injuries with an injury rate of 20.9 injuries per 1000 athlete days 5. Furthermore, the number of acute injuries during contact team sports such as WR and WB is higher than fencing and tennis (61%, 65%, and 42%, 37%, respectively) 6.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors did not analyze the fall-related injuries, but the sports believed to be risky and thus, inseparably connected with falls. Derman et al [41] described sport-related injuries during the winter Paralympics in Peyong Chang in 2018. Most of the injuries were noted during para-snowboard competition, next during alpine skiing, hockey on sledge and crosscountry skiing while the fewest injuries were noted during curling on wheel-chairs.…”
Section: Discussionmentioning
confidence: 99%